Enabling environment for agricultural growth and competitiveness: Evaluation, indicators and indices - Díaz-Bonilla, Eugenio; Orden, David; Kwieciński, Andrzej (OECD Publishing, 2014)
The key contribution of this report lies in developing a typology to structure the components of the enabling environment for agricultural growth and competitiveness, and in constructing an illustrative Agricultural Growth Enabling Index (AGEI) to summarise a wide array of available information in a coherent manner. The construction of the preliminary AGEI is based on four blocks with 40% of the weight on agriculture/rural factors and 20% each on broader economy-wide governance, capital availability and market operation.